CRITICAL REVIEW IN NURSE TECHNICIANS IN HEALTHCARE DELIVERY - ASSESSING THEIR CONTRIBUTIONS TO PATIENT CARE AND CLINICAL SUPPORT - 1Hamad Salem Alshahi, 2Ayed Hamad Al Alshahi, 3Abdullah, Mohammed Mana alyami, 4Hamad Mohammad Hamad Alabbas, 5Ail Mohammad Hamad Alabbas, 6Tariq Mohammed Hamed Al Hodasan, 7Ali Mohamed Salih ALhokash, (Chelonian Research Foundation, 2022)
Nurse technicians are integral to modern healthcare systems, providing crucial support to nurses and significantly impacting patient care. This introductory survey assesses physicians' commitment to healthcare centered on patient care and therapeutic help. It builds on existing writing and investigates their parts, challenges, and benefits in bunch treatment. This article highlights the significance of satisfactory preparation, supervision, and accreditation and recommends methodologies to extend the influence of healthcare experts. By analyzing distinctive thoughts, it appears the significance of specialists in making strides toward patient results and progressing the quality of treatment. Top of Form Keywords: nurse technicians, healthcare delivery, patient care, clinical support, roles, responsibilities, training